(untitled) (International journal of medical sciences, 2026)
This article analyzes the methodological foundations for the formation and development of creative thinking among students in the process of teaching histology. In modern medical education, along with deep mastery of theoretical knowledge, the development of students’ independent, critical, and creative thinking skills is of great importance. The study evaluates the effectiveness of problem-based learning, cluster methods, case-study approaches, digital microscopy, 3D modeling, and the use of interactive platforms based on experimental research. The results demonstrate that in classes organized using creative approaches, students’ academic performance and analytical thinking abilities significantly increased.